Preparation of Siam Weed extracts / Nor Shamsiah Mohamed and Koh Ching Theng - Mohamed, Nor Shamsiah; Koh, Ching Theng (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2018)
Siam Weed is a perennial shrub in the Asteraceae family that spreads throughout tropical and subtropical areas of the world. Siam weed has been used as a traditional herbs for ailments such as fever and soft tissue wounds. Previous studies show potential utilization of Siam weed extracts in medical areas. This study is aimed to produce Siam weed extracts to be used to further exploit its application in medical products. We first repeated step of preparation for Siam weed crude extract and then modified the steps to develop a new way of preparation of Siam weed aqueous extract that is suitable for further development of medical application. The chemical properties of the aqueous extract were investigated using Fourier transform infrared spectroscopy (FTIR). This characterization results revealed that the Siam weed aqueous extract was successfully prepared and its chemical properties are similar to that of crude extracts. By maintaining similar chemical properties, Siam weed aqueous extract can be useful to further exploitation of Siam weed extracts in medical applications.